Videodrome [videorecording (DVD)] - Cronenberg, David, 1943-; Woods, James, 1947-; Smits, Sonja, 1958-; Harry, Debbie (Universal Home Video, 1998)
Cable TV programmer Max Renn seeks out the ultimate in bizarre shows for his channel. He meets a mysterious supplier named Harlan who gives him access to an underground sex and violence network called "Videodrome."